IDO1 inhibits ferroptosis by regulating FTO-mediated m6A methylation and SLC7A11 mRNA stability during glioblastoma progression - Qianting Tian; Guixue Dan; Xuyan Wang; Jiamei Zhu; Chaochun Chen; Dekun Tang; Ziming Wang; Dan Chen; Shan Lei; Chao Yang; Houmei Wang; Bing Guo; et al. (Cell Death Discovery)
Abstract Indoleamine 2, 3-dioxygenase 1 (IDO1) has been recognized as an enzyme involved in tryptophan catabolism with immunosuppressive ability. This study determined to investigate the impact of IDO1 on glioblastoma multiforme (GBM) cells. Here, we showed that the expression of IDO1 was markedly increased in patients with glioma and associated with GBM progression. IDO1 overexpression suppressed ferroptotic cell death, reduced ROS and lipid peroxide generation in GBM cells. IDO1 expression increased the SLC7A11 mRNA stability through FTO-dependent m6A methylation. Mechanistically, IDO1 promoted the AhR expression and nuclear translocation, thus facilitating AhR recruitment at the promoter regions of FTO gene and negatively regulating its transcription. These findings demonstrate that IDO1 facilitates GBM progression by inhibiting SLC7A11-dependent ferroptosis through an IDO1-AhR-FTO axis-mediated m6A methylation mechanism.